THE ASSOCIATION OF PERFORMANCE, AWARDS, OWNERSHIP, AND MEDIA WITH THE ENVIRONMENTAL DISCLOSURE - Adita Mutiara Annisa; Husnah Nur Laela Ermaya (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2022)
This research aims at analyzing and empirically testing the effect of environmental performance, environmental awards, institutional ownership, and media coverage at 32 non-financial companies listed on the Indonesia Stock Exchange and PROPER for the period 2018 – 2020 with 96 data and analyzed using multiple regression. The result of the statistical tests has proven that institutional ownership has a significantly negative effect on environmental disclosure. Meanwhile, environmental performance, environmental awards, and media coverage do not affect environmental disclosure.